2004
DOI: 10.1084/jem.20041328
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Bim Increases T Cell Production and Function in Interleukin 7 Receptor–deficient Mice

Abstract: Interleukin (IL)-7 receptor (R) signaling is essential for T and B lymphopoiesis by promoting proliferation, differentiation, and survival of cells. Mice lacking either IL-7 or the IL-7Rα chain have abnormally low numbers of immature as well as mature T and B lymphocytes. Transgenic expression of the apoptosis inhibitor Bcl-2 rescues T cell development and function in IL-7Rα–deficient mice, indicating that activation of a proapoptotic Bcl-2 family member causes death of immature and mature T cells. BH3-only pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 24 publications
(46 reference statements)
5
113
0
Order By: Relevance
“…45 Indeed, when BIM-deficient animals were bred to IL-7R-deficient mice, there was a partial rescue of thymocytes development and a near restoration of mature T-cells in the periphery. 46 These data imply that while BIM is not the sole mediator of apoptosis in developing T-lymphocytes, it plays a substantial role in mediating death downstream of growth factor withdrawal. It has been demonstrated that loss of PUMA in cultured myeloid cells rendered these cells resistant to growth factor withdrawal.…”
Section: Cytokines Regulate Survival In Early Lymphocyte Developmentmentioning
confidence: 99%
“…45 Indeed, when BIM-deficient animals were bred to IL-7R-deficient mice, there was a partial rescue of thymocytes development and a near restoration of mature T-cells in the periphery. 46 These data imply that while BIM is not the sole mediator of apoptosis in developing T-lymphocytes, it plays a substantial role in mediating death downstream of growth factor withdrawal. It has been demonstrated that loss of PUMA in cultured myeloid cells rendered these cells resistant to growth factor withdrawal.…”
Section: Cytokines Regulate Survival In Early Lymphocyte Developmentmentioning
confidence: 99%
“…Bim is crucial not only for eliminating lymphocytes that recognize self-antigens, during the development of both T cells [45] and B cells [46], but also for terminating T cell immune responses [47,48]. Furthermore, the lymphopenia provoked by loss of the Interleukin-7 receptor is alleviated by loss of Bim [49]. Bim also ensures the death of granulocytes [50], osteoclasts [34], mast cells [51] and neurons [52,53] upon cytokine deprivation.…”
Section: Physiological and Pathological Functions Of Bh3-only Proteinsmentioning
confidence: 99%
“…As Bim is critical for cytokine deprivation-induced apoptosis in diverse hematopoietic cell subsets [5,16], it was concluded that growth factor withdrawal kills cells through transcriptional upregulation of Bim by Foxo3a [11][12][13][14].…”
Section: Identification Of Foxo-binding Sites In the Bim Promotersmentioning
confidence: 99%